But do they agree? Examining differences in science faculty and student perceptions’ of the presence of student partnership values - Chittle, Laura; Coyne, Paige; King, Aliyah; Sood, Siddhartha; Houser, Chris; Cavallo-Medved, Dora (International Journal for Students as Partners, 2023)
There is growing support for the use of student-faculty partnerships within higher education. Successful partnerships, capable of sustainable transformation, require the presence of several underlying values held by both faculty and students. The purpose of this study was to examine differences in the perceptions of student-faculty partnership values across science faculty, graduate and undergraduate students, and determine whether these values differ by partnership category. Faculty and students responded to the Student Staff Partnership Questionnaire which included five scales aimed to assess values for successful student partnerships: reciprocal respect, influence, autonomy, commitment, and partnership. Our findings suggest that faculty perceive themselves as aligning with the values of reciprocal respect, influence, autonomy, and partnership to a higher degree than undergraduate and graduate students perceive faculty as adhering to them. No differences in values were noted across partnership categories. Implications for higher education are discussed.